The development of cold chipping potato parental lines for breeding cultivars suitable for processing - Domański, Leszek; Zimnoch-Guzowska, Ewa; Domańska, Maria; Jakuczun, Henryka; Zgórska, Kazimiera; Frydecka-Mazurczyk, Anna (Plant Breeding and Seed Science, 2004)
The objective of this research was to determine if variation for cold chipping exists in two breeding populations 4×-4× and 4×-2× potato hybrids. Twenty four potato genotypes of a population of 4×-4× hybrids (originated from crosses between parents with good chipping quality) were tested under field conditions at Młochów Research Center of the Plant Breeding and Acclimatization Institute over three years. Traits evaluated included: total tuber yield, marketable yield, starch content, chip colour after cold storage at 4°C, content of reducing sugars, tuber appearance. Out of 24 tested clones three have been selected with outstanding low accumulation of reducing sugars after cold storage (4°C), stable light chip colour and increased starch content. They were also described in trials as having moderate yielding ability, good tuber appearance and satisfied level of resistance to PVY, PLRV and Phytophthora infestans. Of four tested diploid parents in 4×-2× crosses, the DG 93-332 and the HT/HZ84-PH-151 were more suitable for creation of tetraploid generations combining low content of glucose with increased starch content, good yielding ability and satisfied tuber appearance.